Selective Removal of the Selenocysteine tRNA([Ser]Sec) Gene (Trsp) in Mouse Mammary Epithelium - Kumaraswamy, Easwari (American Society for Microbiology, 2003)
Mice homozygous for an allele encoding the selenocysteine (Sec) tRNA([Ser]Sec) gene (Trsp) flanked by loxP sites were generated. Cre recombinase-dependent removal of Trsp in these mice was lethal to embryos. To investigate the role of Trsp in mouse mammary epithelium, we deleted this gene by using transgenic mice carrying the Cre recombinase gene under control of the mouse mammary tumor virus (MMTV) long terminal repeat or the whey acidic protein promoter. While both promoters target Cre gene expression to mammary epithelium, MMTV-Cre is also expressed in spleen and skin. Sec tRNA([Ser]Sec) amounts were reduced by more than 70% in mammary tissue with either transgene, while in skin and spleen, levels were reduced only with MMTV-Cre. The selenoprotein population was selectively affected with MMTV-Cre in breast and skin but not in the control tissue, kidney. Moreover, within affected tissues, expression of specific selenoproteins was regulated differently and often in a contrasting manner, with levels of Sep15 and the glutathione peroxidases GPx1 and GPx4 being substantially reduced. Expression of the tumor suppressor genes BRCA1 and p53 was also altered in a contrasting manner in MMTV-Cre mice, suggesting greater susceptibility to cancer and/or increased cell apoptosis. Thus, the conditional Trsp knockout mouse allows tissue-specific manipulation of Sec tRNA and selenoprotein expression, suggesting that this approach will provide a useful tool for studying the role of selenoproteins in health.